2011
DOI: 10.1039/c0gc00809e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Cu–Ru/carbon nanotube catalyst for hydrogenolysis of glycerol to 1,2-propanediol via hydrogen spillover

Abstract: A Cu-Ru nanoparticle catalyst supported on carbon nanotubes was prepared by a chemical replacement reaction between Cu metal nanoparticles and Ru 3+ cations. The as-prepared catalyst was characterized by X-ray diffraction, X-ray photoelectron spectroscopy, H 2 and CO chemisorption, and transmission electron microscopy. The results showed that the highly dispersed Ru clusters were present on the external surface of the Cu particles. These tiny Ru clusters did not activate glycerol to carry its hydrogenolysis, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 46 publications
1
55
0
3
Order By: Relevance
“…Marinoiu et al (2009) conducted the hydrogenolysis process with nickel catalyst which resulted in up to 98% 1,2-propanediol selectivity and 30% glycerol conversion in moderate temperature and pressures (200 o C and 20-25 bar, respectively). Recently, Wu et al (2011) reported hydrogenolysis of glycerol to 1,2-propanediol via hydrogen spillover by using Cu-Ru nanoparticle catalyst supported on nanotubes. Another propanediol with numerous applicatons is 1,3-propanediol.…”
Section: Propanediolsmentioning
confidence: 99%
“…Marinoiu et al (2009) conducted the hydrogenolysis process with nickel catalyst which resulted in up to 98% 1,2-propanediol selectivity and 30% glycerol conversion in moderate temperature and pressures (200 o C and 20-25 bar, respectively). Recently, Wu et al (2011) reported hydrogenolysis of glycerol to 1,2-propanediol via hydrogen spillover by using Cu-Ru nanoparticle catalyst supported on nanotubes. Another propanediol with numerous applicatons is 1,3-propanediol.…”
Section: Propanediolsmentioning
confidence: 99%
“…The catalyst was acidic in nature as the presence of Lewis acid sites promoted the glycerol dehydration through acetol intermediate. The conversion and selectivity achieved with this catalyst were higher when compared to CuRu/C as previously reported [18] that yielded some amount of propanol, ethylene glycol, ethanol, methanol, and even CH 4 because of the high activity of Ru catalysts to C-C and C-O bond cleavage.…”
Section: Introductionmentioning
confidence: 38%
“…Wu et al reported the synthesis of 1,2-propanediol from hydrogenolysis of glycerol over a Cu-Ru/carbon nanotube catalyst [120]. The conversions of glycerol and selectivity for the formation of 1,2-propanediol were 99.8% and 86.5%, respectively.…”
Section: Reforming Of Glycerol To Valuable Chemicals By Catalysismentioning
confidence: 99%